The Analysis of factors that influence Profitability In Syariah Bank In Indonesia (Case Study of listed Shariah Bank In Bank Indonwsia from 2008-2012). - Faiza Husnayeni Nahar (IE 13 UMY 004, 2013)
PENELITIAN INI BERTUJUAN UNTUK MENGALISA FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK SAYRIAH YANG TERDAFTAR DI INONESIA.